School Integration of Syrian Refugee Children in Turkey - Murat Kirdar; Ismet Koc; Meltem Dayioglu (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
Although school integration of the children of economic migrants in developed countries is well-studied in the literature, little evidence based on large-scale representative data exists on the school integration of refugee children - many of whom live in low- or middle-income countries. This study focuses on Syrian refugee children in Turkey and examines the underlying causes of native- refugee differences in school enrolment. For this purpose, we use the 2018 Turkish Demographic and Health Survey, which includes a representative sample of Syrian refugee households. Accounting for a rich set of socioeconomic variables, we find that the native-refugee gap in school enrolment drops by half for boys and two-thirds for girls, but the gap persists for both genders. When we restrict the sample to refugees who arrived in Turkey at or before age 8 and account for socioeconomic differences, the native-refugee gap completely vanishes for both boys and girls, indicating that school integration of refugee children in Turkey has been possible conditional on their age at arrival. We also find that the timing of boys' school dropouts coincides with their entry into the labor market, whereas girls' dropouts mostly occur before marriage age. Finally, we reveal important differences between natives and refugees, as well as early and late arrivers among refugees, in never starting school, grade progression and repetition, dropping out, and grade for age.
Keywords: F22; I21; I28; 330; refugees; education; school enrollment; integration; child labor; marriage; Turkey